2013
DOI: 10.1016/j.jebo.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The truth, the whole truth, and nothing but the truth—A multiple country test of an oath script

Abstract: Hypothetical bias is one of the main issues bedeviling the field of nonmarket valuation. The general criticism is that survey responses reflect how people would like to behave, rather than how they actually behave. In our study of climate change and emissions reductions, we took advantage of the increasing bulk of evidence from psychology and economics that addresses the effects of making promises, in order to investigate the effect of an oath script in a contingent valuation survey. The survey was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 46 publications
1
31
0
2
Order By: Relevance
“…Jacquemet et al (2017) found that making a promise can decrease or even eliminate the existence of hypothetical bias. Similarly, Carlsson et al (2013) shows that using an oath script, the share of zero WTP responses and extremely high WTP responses decreases. This approach, however, has been noted for some limitations, including the potential for participants to be bothered by the "heavy handness" of the method (de-Magistris, Gracia, and Nayga 2013).…”
Section: Ex-ante Hypothetical Bias Mitigation Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Jacquemet et al (2017) found that making a promise can decrease or even eliminate the existence of hypothetical bias. Similarly, Carlsson et al (2013) shows that using an oath script, the share of zero WTP responses and extremely high WTP responses decreases. This approach, however, has been noted for some limitations, including the potential for participants to be bothered by the "heavy handness" of the method (de-Magistris, Gracia, and Nayga 2013).…”
Section: Ex-ante Hypothetical Bias Mitigation Methodsmentioning
confidence: 92%
“…This argument is based on evidence from social psychology that tests the effect of making a promise (Albarracín et al 2005;Durantini et al 2006;Girandola and Bernard 2007). Recent studies have investigated the effect of an oath script in environmental studies (Carlsson et al 2013;Jacquemet et al 2011Jacquemet et al , 2013Jacquemet et al , 2017 and food surveys (de-Magistris and Pascucci 2014). Jacquemet et al (2011) suggest that under oath, bidders seem to take both the budget constraint and participation constraint more seriously than with a cheap-talk script.…”
Section: Ex-ante Hypothetical Bias Mitigation Methodsmentioning
confidence: 99%
“…An individual's knowledge on environmental issues may consequently increase the probability of their WTC for environmental protection. Examples of the positive impact of education abound in the literature (Gelissen 2007;Torgler and García-Valiñas 2007;Jones et al 2009Jones et al , 2010Polyzou et al 2011;Halkos and Jones 2012;Carlsson et al 2013).…”
Section: Empirical Model Specificationmentioning
confidence: 99%
“…Finally, household size is expected to be negatively related to an individual's WTC for the environment. Larger households are expected to spend much of their limited budget resources on other needs than giving toward environmental protection (see Carlsson et al 2013).…”
Section: Empirical Model Specificationmentioning
confidence: 99%
“…Subjects who took the oath were on average less likely to either overstate or understate their bids. Carlsson et al (2010) tested the oath in the field using non-market valuation surveys and found that the share of zero WTP responses and extremely high WTP responses decreases, which could be interpreted as reduced dishonesty. Shu et al (2012) find that signing a statement of honesty at the beginning instead of at the end of a self-report serves as a commitment and leads to significant reductions in misreporting.…”
Section: Introductionmentioning
confidence: 99%